The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1055/s-0034-1372637
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Heart Rate Measures during Walking before and after Running Maximal Efforts

Abstract: Previous studies on HR recovery (HRR) measures have utilized the supine and the seated postures. However, the most common recovery mode in sport and clinical settings after running exercise is active walking. The aim of the current study was to examine the reliability of HR measures during walking (4 km · h(-1)) before and following a maximal test. Twelve endurance athletes performed an incremental running test on 2 days separated by 48 h. Absolute (coefficient of variation, CV, %) and relative [Intraclass cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 34 publications
3
60
1
3
Order By: Relevance
“…This wide variation corroborates with the findings of Al Haddad et al 19 , who found large discrepancy in the reliability mea-surements of HRV indexes of the time and frequency domains after exercise in moderately active men. In contrast, Boullosa et al 18 found moderate to high reliability for HRV indexes of the time domain in endurance athletes. One possible explanation for the discrepancy in results between this and other studies 18,19 may be the exercise intensity, since lower intensities generate faster parasympathetic reactivation 30 .…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This wide variation corroborates with the findings of Al Haddad et al 19 , who found large discrepancy in the reliability mea-surements of HRV indexes of the time and frequency domains after exercise in moderately active men. In contrast, Boullosa et al 18 found moderate to high reliability for HRV indexes of the time domain in endurance athletes. One possible explanation for the discrepancy in results between this and other studies 18,19 may be the exercise intensity, since lower intensities generate faster parasympathetic reactivation 30 .…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, Boullosa et al 18 found moderate to high reliability for HRV indexes of the time domain in endurance athletes. One possible explanation for the discrepancy in results between this and other studies 18,19 may be the exercise intensity, since lower intensities generate faster parasympathetic reactivation 30 . In this study, 38.9% of active women reached ≥85% HR max in the 6MWT and 61.1% reached 67-84%, while among sedentary women, only 5.6% (one participant) reached ≥85% HR max and 94.4% reached 59-79% HR max .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Among the techniques used for its evaluation, the analysis of heart rate variability (HRV) through R-R intervals has emerged as a simple and noninvasive technique of autonomic impulses, representing one of the most promising quantitative markers of autonomic equilibrium 15 . The HRV analysis describes the oscillations in the interval between consecutive heart beats (R-R intervals) as well as oscillations between consecutive instant heart rates.…”
mentioning
confidence: 99%